Nem tudo são flores: a (ir)racionalização da violência doméstica contra mulher no agreste da Paraíba - Silva, Allan Jones Andreza (2016)
This work deals with domestic and family violence against women in the 8th Area Public Safety Integrated (8th APSI), located in Mesorregião Agreste of Paraíba State, specifically, based on the inquiry into the constitutive roots of the problem in this region. Therefore, we used the deductive methodological approach, initiated by a historical background on the evolution of women's rights, followed later by theoretical analysis of this form of violence, with a reference intakes of Criminology Critical after Alessandro Baratta, sociology as Pierre Bourdieu and Communication theory Niklas Luhmman, which makes up the theoretical framework that was adopted in research to understand the incidence of violence in the region, which is empirically observed from the criminal data for the years 2014 and 2015 provided by the 4th Battalion of Police Military institution whose constituency that area. Out yet used a functionalist procedural approach, based on the understanding that domestic violence against women in this region need to be analyzed under different approaches, since it is the result of the correlation between various social actions and reactions that systematically interact and is also structurally made up different functionally interconnected elements (patriarchal power, gender differences, symbolic violence, socioeconomic factors, etc.). Thus, we sought to recognize the mechanisms under which operates this form of violence to understand its multiple facets and complexity and thus understand its operation in the investigated environment.